Optimization pitch angle controller of rocket system using improved differential evolution algorithm - Dwi Lastomo; Herlambang Setiadi; Muhammad Ruswandi Djalal (International Journal of Advances in Intelligent Informatics, 2017)
Pitch angle of rocket system is the important parts of the rocket. This part corresponds to the movement of the rocket system. Rocket system is fell into multi-input and multi-output (MIMO) system. The most challenge factor in MIMO system is designing the controller, if the design is not appropriate, it may lead to the unstable condition. Hence, appropriate and robust control design is inevitable. This paper introduces PID controller as pitch angle control of rocket system. Furthermore, PID controller parameter is optimized using improved differential evolution algorithm (IDEA). To analyze the performance of rocket system, time domain simulation is implemented. From the simulation result, it is found by using PID controller based on IDEA, the performance of pitch angle of rocket system is enhanced.